Antibacterial Activity of Fluoxetine-Loaded Starch Nanocapsules - Casagrande-Denardin, J (Elsevier B.V., 2020)
This work proposes the development of a starch-based drug carrier for fluoxetine (FLX) delivery and evaluate the improvement of the drug antibacterial activity. The starch nanocapsules were prepared via interfacial polyaddition reaction presenting a core-shell morphology, based on polyurethane linkage, with a particle size in the range 250–300 nm. Furthermore, FLX-loaded nanocapsules were evaluated regarding antibacterial potential against Staphylococcus aureus (ATCC® 6538P ™) and its clinical strains of methicillin-resistant. As expected, the FLX-loaded presented lower minimum inhibitory concentration (MIC) values, in the range of 190–95 μg mL−1, against all isolated microorganisms in comparison to FLX, 255 μg mL−1. According to results, the FLX-loaded starch nanocapsules have successfully improved drug antibacterial activity, generating promising perspectives on the field of the hydrophilic drug delivery systems. © 2020 Elsevier B.V.